Fig. 61 in Early-middle Cambrian stratigraphy and faunas from northern Siberia ... - Kouchinsky, Artem; Alexander, Ruaridh; Bengtson, Stefan; Bowyer, Fred; Clausen, Sébastien; Holmer, Lars E.; Kolesnikov, Kirill A.; Korovnikov, Igor V.; Pavlov, Vladimir; Skovsted, Christian B.; Ushatinskaya, Galina; Wood, Rachel; et al. (Zenodo, 2022)
Fig. 61. Lobopodian (A) and bradoriid (B–D) calcium phosphatic fragments, from the lower Cambrian Erkeket Formation, Khorbusuonka River (B, C) and Tyuser (D), and Sekten (A) formations, lower reaches of the Lena River, Siberia, Russia; samples 19/3.25 (C), 19/31.75 (B), 21/57.75 (D), and 22/67 (A). A. Microdictyon robisoni Bengtson, Matthews, and Missarzhevsky, 1986, sclerite, SMNH X11294. B. Mongolitubulus spinosus (Hinz, 1987), spine, SMNH Ar75002. C. Mongolitubulus reticulatus Kouchinsky, Bengtson, Clausen, Gubanov, Malinky, and Peel, 2011, spine, SMNH Ar75003. D. Cambria sibirica Neckaja and Ivanova, 1956, carapace, SMNH Ar75001; D1, anterior view; D2, D3, dorsal view. Scale bar: 250 µm A–C) and 1.25 mm (D). ... : Published as part of Kouchinsky, Artem, Alexander, Ruaridh, Bengtson, Stefan, Bowyer, Fred, Clausen, Sébastien, Holmer, Lars E., Kolesnikov, Kirill A., Korovnikov, Igor V., Pavlov, Vladimir, Skovsted, Christian B., Ushatinskaya, Galina, Wood, Rachel & Zhuravlev, Andrey Y., 2022, Early-middle Cambrian stratigraphy and faunas from northern Siberia, pp. 341-464 in Acta Palaeontologica Polonica 67 (2) on page 424, DOI: 10.4202/app.00930.2021, http://zenodo.org/record/12198251 ...